Penyuluhan Hukum Pencegahan Kekerasan Dalam Rumah Tangga di Desa Persiapan Belongas - Sa'diyah, Nur Khalimatus; Enggarsasi, Umi (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
Community service is carried out by the proposing team in the form of legal socialization which aims to optimize and increase understanding and legal awareness of the community. Domestic violence is a complex issue in almost every country that is rampant due to the lack of empathy, understanding of victims and the surrounding environment to make reports related to domestic violence cases. Preventive efforts to reduce and eliminate domestic violence can be done through repressive efforts for the perpetrators and also preventive efforts as a prevention of domestic violence. The causes of domestic violence include a lack of public understanding of the act of domestic violence itself. The role of universities in preventing domestic violence by providing knowledge in the form of legal socialization for the public is not only limited to women and children but also for men. Legal socialization aims to increase public insight into legal efforts related to domestic violence so as to increase their awareness not to commit domestic violence. The community service team conducted legal socialization in the preparatory village of belongas, Sekotong sub-district, West Lombok as a preparatory village before being made a definitive village.